A City between the Global and the National: U.S. Navy's Peacemaking Mission in Split, 1918-1921. - Perica, Vjekoslav; Stokes, Gale; Jakovina, Tvrtko Aleksić, Vesna; Gordon N. Bardos Hayden, Robert, M.; Raymond, Gregory, A. Visković, Ivo; Trgovčević, Ljubinka (2008)
Article uses US naval archives to analyze one of earliest successful peacekeeping operations in history. One of reasons for success was US navy's management of a complex situation but also interaction with the local community.
MZOŠ-u je 2008. prijavljen projekt "Mirovna misija saveznika u Dalmaciji 1918.-1921 prema arhivima mornarice SAD".
ENG